PENGARUH BOOK TAX DIFFERENCE DAN ARUS KAS OPERASI TERHADAP PERSISTENSI LABA PADA PERUSAHAAN SEKTOR PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Willy Nurhayadi; Saeful Fachri; Maulia Diani (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This research was conducted to determine the effect of Book Tax Difference and Operating Cash Flow on Earnings Persistence in the Property and Real Estate Sector Companies listed on the Indonesia Stock Exchange. This research uses descriptive statistical analysis research type with a quantitative approach, with secondary data collection techniques. The sampling technique used was the purposive sampling technique. The sample is 64 of 16 companies in the Property and Real Estate Sector multiplied by a period of 4 years. The analytical method used in this study is Multiple Linear Regression Analysis with the help of SPSS 26 program. The results of this study indicate that Book Tax Difference has no effect on Earnings Persistence and Operating Cash Flow has a significant positive effect on the Earnings Persistence. The F test shows that the variables of Book Tax Difference and Operating Cash Flow has a significant positive effect on Earnings Persistence